Підвищення ефективності передачі пакетів інформації в сенсорних та локально-регіональних радіомережах для організації зв’язку між мобільними роботами і рухомими системами - Шевчук, Б.М. (Штучний інтелект, 2011)
У статті запропоновані методи і алгоритми комплексної обробки і кодування моніторингової інформації, масивів даних для формування і передачі компактних криптостійких та завадостійких пакетів інформації, а також для зв’язку між віддаленим центром управління, збору і передачі інформації та мобільними системами. Запропоновано оперативно визначати амплітудно-часові характеристики суттєвих відліків сигналів і відеосигналів, включаючи екстремуми і точки перегину, а вихідні потоки даних кодувати різницевими кодами. Після стиску даних без втрат бітові послідовності заданої величини шифруються з урахуванням
необхідного ступеня захисту інформації. Завадостійка передача пакетів інформації досягається за рахунок перемішування даних і передачі шумоподібних пакетів з мінімально необхідною базою. The article, based on the methodology of information and efficient processing, coding and packet transmission in radio networks, proposes the methods and algorithms for complex processing and coding of monitoring information (signals and video signals), data sets for the generation and transmission of compact, reliable and error-correcting packets of information in local-regional wireless sensor networks with self-organization
transfer of information to implement the communication between mobile robots and mobile systems, as well as for communication between a remote control center, data acquisition and transmission and mobile systems. In the process of data compression with acceptable loss, in the article it is proposed to determine quickly the amplitude-temporal characteristics of the material samples and video signals, including extremes
and inflection points, and to encode output data streams by difference codes. After lossless data compression, bit sequences given value is encrypted with the necessary degree of information security. Noise-proof transmission of information packets is achieved through the mixing of data and transmission of noise-like packages with the minimum of necessary facilities.